Review of Literature: The Impact of Competitive Advantage on Business Marketing Performance - Irawan, Edi; Sudarmiatin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to thoroughly investigate the impact of competitive advantage on the marketing performance of businesses. Companies possessing a competitive advantage consistently demonstrate an understanding of changes in market structure and the ability to choose effective marketing strategies. Competitive advantage can be achieved through various means, such as offering high-quality products or services, establishing uniqueness compared to competitors, or targeting specific market segments. Recognizing how to sustain a competitive advantage is a key factor in a company's success in a competitive environment. In summary, the roles of competitive advantage in the marketing performance of business actors include its impact on company performance, increasing business profits, influencing financial performance, affecting work performance, and shaping buyer decisions